2021
DOI: 10.3390/ani11102793
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Risk Factors of Anaplasma spp. in German Small Ruminant Flocks

Abstract: Knowledge about the distribution of Anaplasma spp. in small ruminants from Germany is limited. Therefore, serum samples were examined from 71 small ruminant flocks (2731 sheep, 447 goats) located in the five German federal states: Schleswig-Holstein (SH), Lower Saxony (LS), North Rhine-Westphalia (NRW), Baden-Wuerttemberg (BW) and Bavaria (BAV). Antibodies to Anaplasma spp. were determined by a cELISA based on the MSP5 antigen. A risk factor analysis at animal and flock level was also performed. Antibodies to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…MSP5 is a transmembrane protein of 210 amino acid residues that is present in all recognized Anaplasma species and that is highly conserved among different strains of A. marginale , A. centrale , A. ovis and A. phagocytophilum [ 19 ]. It has been used in the sero determination of Anaplasma infection in animals, and among the methods of serodetection, indirect ELISA and competitive ELISA are considered reliable [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 36 ]. The MSP5 protein in this study was expressed with 182 amino acids whose signal peptide was removed to develop an indirect ELISA for detecting antibodies against A. marginale , A. centrale , A. ovis, and A. phagocytophilum and to screen carrier animals for infection with Anaplasma species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MSP5 is a transmembrane protein of 210 amino acid residues that is present in all recognized Anaplasma species and that is highly conserved among different strains of A. marginale , A. centrale , A. ovis and A. phagocytophilum [ 19 ]. It has been used in the sero determination of Anaplasma infection in animals, and among the methods of serodetection, indirect ELISA and competitive ELISA are considered reliable [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 36 ]. The MSP5 protein in this study was expressed with 182 amino acids whose signal peptide was removed to develop an indirect ELISA for detecting antibodies against A. marginale , A. centrale , A. ovis, and A. phagocytophilum and to screen carrier animals for infection with Anaplasma species.…”
Section: Discussionmentioning
confidence: 99%
“…This study tested a total of 1732 bovines and found that 5.0% (87/1732) were Anaplasma IgG positive, 4.2% (73/1732) were Anaplasma IgM positive and 1.4% (24/1732) were both IgG and IgM positive, indicating that bovines are among those animals that can develop acute infections and middle and late infections in this plateau area. Moreover, sheep and goats can become infected with obligate intracellular bacteria of the genera Anaplasma , A. phagocytophilum and A. ovis , leading to the development of ovine and caprine anaplasmosis [ 18 , 28 , 32 ]. The present results showed not only a high IgG-positive rate (25.8%) but also a 5.8% IgM antibody positivity in Tibetan sheep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibodies against Anaplasma spp., C. burnetii and TBEV were determined by three different commercial ELISAs in accordance with the manufacturers’ instructions and described in detail elsewhere [ 1 , 17 , 18 ]. An inhibition of ≥ 30% was assessed as positive for the Anaplasma spp.…”
Section: Resultsmentioning
confidence: 99%
“…by cELISA is not possible. [ 30 ]. Studies have suggested serological cross-reactions between A. phagocytophilum and other Anaplasma spp.…”
Section: Discussionmentioning
confidence: 99%